The comparative analysis of map projections for the Republic of Moldova territory - Chiriac, V.; Vlasenco, A. (Видавництво Львівської політехніки, 2016)
Starting from 2001 a new reference system MOLDREF99 based on European Terrestrial Reference System (ETRS89) and Transversal Mercator for Moldova (TMM) map projection was established to provide large scale mapping from 1:500 to 1:10 000. However, the deformations on the margins of the 3,5 degree zone are not fitting requirements for 1:500 mapping. In this case for marginal zones a new scale coefficient has to be used in order to reduce deformations. This circumstance complicates many geodetic applications: geodetic works, cadastral surveying, GIS, mapping, etc. This paper presents the results of study of Oblique Mercator map projection for large scale mapping of territory of our country in order to reduce deformations on the margin of the zone. Comparative study of TMM (Transverse Mercator for Moldova) map projection, currently used for large scale mapping, and Oblique Mercator map projection showed the reduction of deformations on the center from 6 to 2 cm/km and on the margins of the zone from 16 to 8 cm/km. The analyses of Stereo 70 map projection in comparison with both studied map projection showed than relative linear distortions from ±15 cm/km to ±35 cm/km of more than 8 % of country territory and cannot be used as a unique map projection for large scale mapping for all territory of the country. The results of this study could be used for argumentation of new Oblique Mercator map projection for large scale mapping to be adopted by Land Relation and Cadastre Agency. Наведено результати дослідження картографічної проекції Меркатора для великомасштабного картування території Молдови з метою зменшення деформацій на краях зон. Представлены результаты исследования картографической проекции Меркатора для крупномасштабного картирования территории Молдовы с целью уменьшения деформации на краях зон.
Порівняльний аналіз картографічних проекцій для території Республіки Молдова
Сравнительный анализ картографических проекций для территории Республики Молдова
Keywords: reference system; map projection; central meridian; relative linear deformations